ASSOCIATION OF SERUM SIALIC ACID AND SERUM URIC ACID LEVELS WITH FASTING BLOOD GLUCOSE LEVELS IN TYPE-2 DIABETES MELLITUS PATIENTS - PASCAL SINGH, YENDREMBAM; SINGH PUNIA, VED PAL; RAI, GLADYS; NANDKEOLIAR, MANOJ KUMAR (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objectives: The objective of the study was to estimate the serum sialic acid and serum uric acid levels in patients with type-2 diabetes mellitus and non-diabetic individuals and determining the association of serum sialic acid and serum uric acid levels with fasting blood glucose levels in patients with type-2 diabetes mellitus and also in non-diabetic individuals. Methods: The study was a cross-sectional analysis where 70 individuals in the age group of 30–70 years participated during 6 months period. This included two groups, one for type-2 diabetes patients as cases and other non-diabetics as controls. In each group, 35 individuals participated. There were 15 males and 20 females in type-2 diabetic group and 16 males and 19 females in non-diabetic group. Fasting blood glucose, serum sialic acid, and serum uric acid were estimated in both the groups. Results: In this study, the serum sialic acid levels of type-2 diabetes mellitus were shown to be increased (76.60 ± 7.89) when compared to non-diabetics (39.66 ± 9.55) with a statistically significant, p < 0.001. The serum uric acid concentrations were also found to be slightly elevated in type-2 diabetes mellitus (4.48 ± 0.79) when compared to non-diabetics (4.28 ± 0.89) with a statistically non-significant, p = 0.323. Conclusion: Based on this study, it is concluded that serum sialic acid and serum uric acid levels have been found to be positively associated with type- 2 diabetes mellitus in both men and women, indicating the risk of developing microvascular complications in those patients. Therefore, estimating the sialic acid and uric acid levels can aid in the early diagnosis and prevention of microvascular complications caused by type-2 diabetes mellitus.